Plant Proteomics (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
This special issue on "Plant Proteomics" aims to highlight the diverse applications of proteomics in understanding plant molecular responses to various biotic and abiotic challenges. Recent advancement in mass spectrometry, complemented with the availability of more complete genome-sequence data and modern bioinformatics, has made proteomics a fast, sensitive and reliable technique to identify and characterize novel proteins and to follow temporal changes in protein relative abundances under adverse environmental conditions. This issue includes 4 reviews and 8 original articles primarily on environmental proteomics studies.